Geospatial Study of Human Development Index of Ukraine in the Light of Regional Indicators - Kuzyshyn, Andriy (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2014)
The article reveals the peculiarities in the formation of comfortable life features in the regions of Ukraine based on the analysis of the components and the human development index. In particular, it reveals the essenceof the human development concept as one that enables people to develop their potential, to live productively and creatively in tune with their needs and interests. Its goal is to empower each individual in the chosen environment - country, region or specific locality. Human development involves balancing the formation of human abilities to improve their conditions of life. However, the level of regional human development will depend on the potential of the designated area. Since 2012, Ukraine has updated the method of estimating regional Human Development Index by which we can calculate the regional human development index. It includes 33 indicators grouped into six blocks in accordance with the basic aspects of human development. These are reproduction, social position, comfortable life, well-being, worthy work, and education. These indicators were selected on the basis of suitability for the annual calculation of provision available to the State Statistics Service of Ukraine, reliability estimates at the regional level under the specific issues of human development in Ukraine, unambiguous interpretation of the impact on human development, lack of high correlation between individual performance and adequacy of static and dynamic variation. According to the ratings of Human Development Index in 2012, conducted by the State Statistics Service of Ukraine and the Institute of Demography and Social Studies of M.V. Puhta, regions that constantly show high indicators of human development index are Crimea, Kharkiv, Lviv, Transcarpathian and Poltava regions. The largest group consists of regions with the average index indicator of the human development (most regions of Ukraine). Finally, the third group consists of regions with the lowest human development index (Kirovograd, Donetsk, Sumy regions). The results of calculations of regional Human Development Index can serve as a basis for identifying key issues and priorities of each region.